Early-strength steam-curing-free high-content fly ash cement-based composite material as well as preparation method and application thereof

By adding a variety of active ingredients and polymer exciters to high-content fly ash cement-based composites, the problems of low strength and slow curing speed are solved in the early stage, and the early strength effect is achieved without steaming, reducing energy consumption and carbon emissions, and improving production efficiency and material value.

CN119504204APending Publication Date: 2025-02-25SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411578265.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing high-content fly ash cement-based composite materials have low strength and slow curing speed in the early stages, and require steaming and curing treatment to improve strength and curing speed, resulting in increased energy consumption and carbon emissions and extended production costs and time.

Method used

By adding a variety of active ingredients, such as alkaline alumina, calcium oxide, calcium sulfate, sodium fluorosilicate, ultrafine hydrated calcium silicate and calcium formate, as well as acidic active ingredients, such as sulfa aluminate cement, polymer aluminum sulfate, ultrafine silica powder and ultrafine acidic alumina, combined with polymer exciters, we form early-strength, steam-free and high-content fly ash cement-based composites.

Benefits of technology

It realizes that high-content fly ash cement-based composite materials with high early strength and short curing time can be obtained without steaming, reducing energy consumption and carbon emissions, improving production efficiency, and enhancing the economic value of the materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an early-strength steam-curing-free high-content fly ash cement-based composite material as well as a preparation method and application thereof, and the method comprises the following steps: 1, uniformly mixing cement, superfine fly ash and fine fly ash to obtain a component A; 2, mixing alkaline aluminum oxide, calcium oxide, calcium sulfate, sodium fluosilicate, superfine hydrated calcium silicate and calcium formate, and grinding to obtain a component B; 3, sulphoaluminate cement, polyaluminum sulfate, superfine silicon dioxide powder and superfine acidic aluminum oxide are mixed and ground, and a component C is obtained; and 4, adding water into a polymer activator solution with the solid content of 50% to obtain a diluted polymer activator solution, adding the diluted polymer activator solution into a mixture of the component A, the component B and the component C, and uniformly stirring to obtain the early-strength steam-curing-free high-content fly ash cement-based composite material. The high-content fly ash cement-based composite material with high early strength can be obtained without steam curing, energy consumption and carbon emission are reduced, and production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cement-based composite material, in particular to an early-strength, steam-curing-free, high-content fly ash cement-based composite material and a preparation method and application thereof. Background Art

[0002] In my country, coal is mainly used for coal-fired power generation and coal chemical industry, which consume 80% of coal production. In coal-producing areas, there are a large number of coal chemical industry and coal-fired power generation enterprises, which generate a large amount of solid waste every year. Among the solid waste, fly ash has the largest amount. A large amount of fly ash and other solid wastes need to be piled up and stored, occupying a large area of ​​land.

[0003] The use of fly ash and cement to prepare cement-based composite materials with a fly ash content of more than 50% can effectively reduce the stacking of fly ash. However, studies have found that cement-based composite materials with a fly ash content of more than 50% have very low strength in the early stage and a slow curing speed. In the later stage, steam curing is required to improve the curing speed and high compressive strength, thereby shortening the time for preparing various cement-based composite products (for example, cement floor tiles, cement pipes, cement hollow bricks, cement decorative building materials, etc.), thereby improving the economic value of fly ash. However, steam curing not only increases the energy loss and carbon emissions of the production process, but also prolongs the time, ultimately increasing the production cost of cement-based composite materials and reducing production efficiency.

[0004] Therefore, how to shorten the curing time of high-content fly ash-based cement composites, improve their early strength, and reduce energy loss and carbon dioxide emissions in the production process are issues that need to be urgently addressed in the preparation of high-content fly ash-based cement composites. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an early-strength, steam-free, high-content fly ash cement-based composite material and a preparation method and application thereof. A high-content fly ash cement-based composite material with high early strength and short curing time can be obtained without steaming, thereby reducing energy consumption and carbon emissions and improving production efficiency.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing an early-strength, steam-free, high-content fly ash cement-based composite material comprises the following steps:

[0008] Step 1: Mix 350-390 parts of cement, 780-840 parts of ultrafine fly ash, and 840-930 parts of fine fly ash uniformly according to weight to obtain component A;

[0009] Step 2: According to the weight percentage, 9 to 14 parts of basic alumina, 8 to 13 parts of calcium oxide, 4 to 9 parts of calcium sulfate, 6 to 9 parts of sodium fluorosilicate, 7 to 10 parts of ultrafine hydrated calcium silicate and 4 to 7 parts of calcium formate are mixed and ground to obtain component B;

[0010] Step 3, according to the mass parts, 9 to 14 parts of sulphoaluminate cement, 8 to 13 parts of polyaluminium sulfate, 11 to 13 parts of ultrafine silica powder and 7 to 10 parts of ultrafine acidic alumina are mixed and ground to obtain component C;

[0011] Step 4: First, add 10 to 14 parts of a polymer activator solution with a solid content of 50% into 120 to 140 parts of water, according to the mass fraction, to obtain a diluted polymer activator solution; then add the diluted polymer activator solution into a mixture of 1970 to 2160 parts of component A, 38 to 62 parts of component B and 35 to 50 parts of component C, stir evenly, and obtain an early-strength, steam-free, high-content fly ash cement-based composite material.

[0012] Furthermore, the cement in step 1 is ordinary Portland cement with a label of P·O 42.5.

[0013] Furthermore, the particle size of the ultrafine fly ash in step 1 is 0.4-0.6 μm, the particle size of the fine fly ash is 50-90 μm, and the ignition loss of the ultrafine fly ash and the fine fly ash is not more than 3.2%, the water requirement is not more than 91%, the water content is not more than 0.2%, the activity index is 85-90%, and the specific surface area is 2600-3100 m 2 / kg.

[0014] Furthermore, the calcium sulfate in step 2 is calcium sulfate dihydrate.

[0015] Furthermore, the particle size of the ultrafine hydrated calcium silicate in step 2 is 0.5 to 0.9 μm.

[0016] Furthermore, the polyaluminium sulfate in step 3 has a basicity of 50% and a pH value of its aqueous solution of 5-9.

[0017] Furthermore, the particle size of the ultrafine silicon dioxide powder in step 3 is 0.2-0.6 μm, the loss on ignition is less than 3.0%, and the SiO2 content is greater than 90%.

[0018] Furthermore, the particle size of the ultrafine acidic alumina in step 3 is 0.3-0.8 μm.

[0019] Furthermore, the grinding in step 2 and step 3 is performed using an ultrafine grinding mill for 1 to 2 minutes.

[0020] Furthermore, the polymer activator solution in step 4 is a polyethyleneimine solution with a pH value of 9.0, and the average relative molecular mass of the polyethyleneimine is 3000.

[0021] An early strength, steam-curing-free, high-content fly ash cement-based composite material, wherein the fly ash content is 72.63% to 74.41% and the 3h compressive strength is greater than 12MPa.

[0022] The invention discloses an application of an early-strength, steam-curing-free, high-content fly ash cement-based composite material in the preparation of cement-based composite parts.

[0023] Compared with the prior art, the present invention has the following technical effects:

[0024] The early-strength, steam-curing-free, high-content fly ash cement-based composite material prepared by the invention comprises a basic component and an active component, wherein: the basic component is composed of cement and fly ash, the active component comprises an alkaline active component composed of alkaline alumina, calcium oxide, calcium sulfate, sodium fluorosilicate, ultrafine hydrated calcium silicate and calcium formate, and an acidic active component composed of sulphoaluminate cement, polyaluminium sulfate, ultrafine silica powder and ultrafine acidic alumina; when the basic component, the alkaline active component and the acidic active component are mixed with a polymer activator, not only complex chemical reactions will occur between the two active components, but also complex chemical reactions will occur between the two active components and the polymer activator, cement and fly ash, ultimately promoting complex chemical reactions between cement, fly ash and active components, and the speed of forming the chemical reaction is faster than the hydration reaction of conventional cement, and a structurally stable inorganic macromolecular structure can be formed more quickly, and the structure has higher strength, so that higher early strength can be obtained without steam curing.

[0025] The present invention adds a variety of active ingredients to the fly ash produced by coal chemical industry and coal-fired power generation to obtain an early-strength, steam-free, high-content fly ash cement-based composite material with a fly ash content of up to 72.63% to 74.41%. This not only improves the utilization rate of fly ash and reduces the land occupation and environmental pollution problems caused by fly ash stacking, but also improves the early strength and curing speed of the high-content fly ash cement-based composite material, eliminates the steaming stage, shortens the production cycle of cement-based composite parts, and reduces energy consumption and carbon dioxide emissions. In addition, the 3h compressive strength of the cement-based composite parts extruded from the high-content fly ash cement-based composite material prepared by the present invention can reach more than 12MPa, which is higher than the 3h compressive strength of 5MPa generally recognized in the industry for packaging, stacking and storage, thereby improving the economic value of the high-content fly ash cement-based composite material. DETAILED DESCRIPTION

[0026] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0027] The basic alumina, calcium oxide, calcium sulfate, sodium fluorosilicate, calcium silicate, calcium formate and polyaluminium sulfate used in Examples 1 to 5 are all chemically pure, with a purity greater than 98%.

[0028] The cement used in Examples 1 to 5 is ordinary Portland cement with a label of P·O 42.5.

[0029] The particle size of the ultrafine fly ash selected in Examples 1 to 5 is 0.4-0.6 μm, and the particle size of the fine fly ash is 50-90 μm. The ignition loss of the ultrafine fly ash and the fine fly ash is not more than 3.2%, the water requirement is not more than 91%, the water content is not more than 0.2%, the activity index is 85-90%, and the specific surface area is 2600-3100 m 2 / kg.

[0030] The particle size of the ultrafine hydrated calcium silicate selected in Examples 1 to 5 is 0.5 to 0.9 μm.

[0031] The polyaluminium sulfate selected in Examples 1 to 5 has a basicity of 50% and a pH value of 5 to 9 in its aqueous solution.

[0032] The ultrafine silicon dioxide powder selected in Examples 1 to 5 has a particle size of 0.2 to 0.6 μm, a loss on ignition of less than 3.0%, and a SiO2 content of more than 90%.

[0033] The particle size of the ultrafine acidic alumina selected in Examples 1 to 5 is 0.3 to 0.8 μm.

[0034] The polymer activator solution selected in Examples 1 to 5 is a polyethyleneimine solution with a pH value of 9.0, and the average relative molecular mass of the polyethyleneimine is 3,000.

[0035] Example 1

[0036] Step 1: Mix 350 parts of cement, 780 parts of ultrafine fly ash and 840 parts of fine fly ash uniformly according to weight to obtain component A;

[0037] Step 2: Mix 9 parts of basic alumina, 8 parts of calcium oxide, 4 parts of calcium sulfate dihydrate, 6 parts of sodium fluorosilicate, 7 parts of ultrafine hydrated calcium silicate and 4 parts of calcium formate according to the weight ratio, put them into an ultrafine grinding mill, and grind them for 1 minute to obtain component B;

[0038] Step 3: Mix 9 parts of sulphoaluminate cement, 8 parts of polyaluminium sulfate, 11 parts of ultrafine silica powder and 7 parts of ultrafine acidic alumina according to weight, put into an ultrafine grinding mill, and grind for 1 minute to obtain component C;

[0039] Step 4: first, according to the mass fraction, add 10 parts of a polymer activator solution with a solid content of 50% to 120 parts of water to obtain a diluted polymer activator solution, and then add the diluted polymer activator solution to a mixture of 1970 parts of component A, 38 parts of component B and 35 parts of component C, and stir evenly to obtain an early strength and steam-free high-content fly ash cement-based composite material;

[0040] Step 5: Using an extrusion molding method to make cement floor tiles from the early-strength, steam-free, high-content fly ash cement-based composite material.

[0041] Example 2

[0042] Step 1: Mix 360 parts of cement, 792 parts of ultrafine fly ash and 863 parts of fine fly ash uniformly according to weight to obtain component A;

[0043] Step 2: According to the mass ratio, 10.25 parts of basic alumina, 9.25 parts of calcium oxide, 5 parts of calcium sulfate dihydrate, 7 parts of sodium fluorosilicate, 8 parts of ultrafine hydrated calcium silicate and 5 parts of calcium formate were mixed, put into an ultrafine grinding mill, and ground for 1.2 minutes to obtain component B;

[0044] Step 3, according to the mass parts, 10 parts of sulphoaluminate cement, 9 parts of polyaluminium sulfate, 11.5 parts of ultrafine silica powder and 7.75 parts of ultrafine acidic alumina were mixed, put into an ultrafine grinding mill, and ground for 1.2 minutes to obtain component C;

[0045] Step 4: first, according to the mass fraction, add 11 parts of a polymer activator solution with a solid content of 50% to 125 parts of water to obtain a diluted polymer activator solution, and then add the diluted polymer activator solution to a mixture of 2017.5 parts of component A, 44 parts of component B and 39 parts of component C, and stir evenly to obtain an early strength and steam-free high-content fly ash cement-based composite material;

[0046] Step 5: Using an extrusion molding method to make cement floor tiles from the early-strength, steam-free, high-content fly ash cement-based composite material.

[0047] Example 3

[0048] Step 1: Mix 370 parts of cement, 810 parts of ultrafine fly ash and 885 parts of fine fly ash uniformly according to weight to obtain component A;

[0049] Step 2: According to the mass ratio, 11.5 parts of basic alumina, 10.5 parts of calcium oxide, 6.5 parts of calcium sulfate dihydrate, 7.5 parts of sodium fluorosilicate, 8.5 parts of ultrafine hydrated calcium silicate and 5.5 parts of calcium formate were mixed, put into an ultrafine grinding mill, and ground for 1.5 minutes to obtain component B;

[0050] Step 3, according to the mass parts, 11.5 parts of sulphoaluminate cement, 10.5 parts of polyaluminium sulfate, 12 parts of ultrafine silica powder and 8.5 parts of ultrafine acidic alumina were mixed, put into an ultrafine grinding mill, and ground for 1.5 minutes to obtain component C;

[0051] Step 4: first, according to the mass fraction, add 12 parts of a polymer activator solution with a solid content of 50% to 130 parts of water to obtain a diluted polymer activator solution, and then add the diluted polymer activator solution to a mixture of 2065 parts of component A, 50 parts of component B and 42 parts of component C, and stir evenly to obtain an early strength and steam-free high-content fly ash cement-based composite material;

[0052] Step 5: Using an extrusion molding method to make cement floor tiles from the early-strength, steam-free, high-content fly ash cement-based composite material.

[0053] Example 4

[0054] Step 1: Mix 380 parts of cement, 828 parts of ultrafine fly ash and 908 parts of fine fly ash uniformly according to weight to obtain component A;

[0055] Step 2: According to the mass ratio, 13 parts of basic alumina, 12 parts of calcium oxide, 7.5 parts of calcium sulfate dihydrate, 8.5 parts of sodium fluorosilicate, 9.5 parts of ultrafine hydrated calcium silicate and 6.5 parts of calcium formate were mixed, put into an ultrafine grinding mill, and ground for 1.8 minutes to obtain component B;

[0056] Step 3: Mix 13 parts of sulphoaluminate cement, 12 parts of polyaluminium sulfate, 12.5 parts of ultrafine silica powder and 9.25 parts of ultrafine acidic alumina according to weight proportions, put into an ultrafine grinding mill, and grind for 1.8 minutes to obtain component C;

[0057] Step 4: first, according to the mass fraction, add 13 parts of a polymer activator solution with a solid content of 50% to 135 parts of water to obtain a diluted polymer activator solution, and then add the diluted polymer activator solution to a mixture of 2112.5 parts of component A, 56 parts of component B and 47 parts of component C, and stir evenly to obtain an early strength and steam-free high-content fly ash cement-based composite material;

[0058] Step 5: Using an extrusion molding method to make cement floor tiles from the early-strength, steam-free, high-content fly ash cement-based composite material.

[0059] Example 5

[0060] Step 1: Mix 390 parts of cement, 840 parts of ultrafine fly ash and 930 parts of fine fly ash uniformly according to weight to obtain component A;

[0061] Step 2: According to the weight ratio, 14 parts of basic alumina, 13 parts of calcium oxide, 9 parts of calcium sulfate dihydrate, 9 parts of sodium fluorosilicate, 10 parts of ultrafine hydrated calcium silicate and 7 parts of calcium formate were mixed, put into an ultrafine grinding mill, and ground for 2 minutes to obtain component B;

[0062] Step 3: Mix 14 parts of sulphoaluminate cement, 13 parts of polyaluminium sulfate, 13 parts of ultrafine silica powder and 10 parts of ultrafine acidic alumina according to weight proportions, put into an ultrafine grinding mill, and grind for 2 minutes to obtain component C;

[0063] Step 4: first, according to the mass fraction, add 14 parts of a polymer activator solution with a solid content of 50% to 140 parts of water to obtain a diluted polymer activator solution, and then add the diluted polymer activator solution to a mixture of 2160 parts of component A, 62 parts of component B and 50 parts of component C, and stir evenly to obtain an early strength and steam-free high-content fly ash cement-based composite material;

[0064] Step 5: Using an extrusion molding method to make cement floor tiles from the early-strength, steam-free, high-content fly ash cement-based composite material.

[0065] The early-strength, autoclaved-free, high-content fly ash cement-based composite materials prepared in Examples 1 to 5 can be made into various cement-based composite products, including but not limited to cement floor tiles, cement pipes and cement boards, through extrusion molding.

[0066] In order to facilitate the comparison of the effects of different material ratios on sample performance, the early-strength, steam-free, high-content fly ash cement-based composite materials prepared in Examples 1 to 5 were all made into cement floor tiles, and then the cement floor tiles prepared in Examples 1 to 5 were tested for performance in accordance with GB / T17671-2021 "Test Method for Strength of Cement Mortar" and GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are shown in Table 1;

[0067] It can be seen from Table 1 that the cement floor tiles prepared in Examples 1 to 5 have excellent mechanical properties and durability, which are specifically manifested in: 1) The 3h compressive strength can reach more than 12MPa, which is higher than the generally recognized 3h compressive strength of 5MPa for packaging and stacking storage in the industry, indicating that it has good initial compressive strength; 2) The compressive strength at 1 day, 3 days, 7 days and 28 days and the flexural strength at 3 days, 7 days and 28 days all meet the basic requirements of cement parts in the industry; 3) The 28-day chloride ion permeability grade is level 4, which has good durability; 4) The mass loss after 30 freeze-thaw cycles and the dynamic modulus loss after 30 freeze-thaw cycles are 0he0-0.2% respectively, indicating that it has good anti-freeze performance and is more durable; 5) the carbonization resistance depth is 0.1-0.2mm, and it has good durability; 6) the volume shrinkage rate in 28 days is 0.1-0.11%, indicating that it has good volume stability; the above is sufficient to illustrate that the early-strength, steam-free, high-content fly ash cement-based composite materials prepared in Examples 1 to 5 have good working performance, volume stability and durability, and are suitable for making different types of cement-based composite parts.

[0068] Table 1 Performance of cement floor tiles prepared in Examples 1 to 5

[0069] Example 1 Example 2 Example 3 Example 4 Example 5 Fly ash content (%) 74.41 72.63 73.69 73.43 73.08 1h compressive strength (MPa) 5.63 5.78 5.78 6.52 6.85 3h compressive strength (MPa) 12.32 13.25 15.61 16.23 16.45 1d compressive strength (MPa) 20.13 22.42 23.52 23.84 29.56 3d compressive strength (MPa) 35.65 37.85 38.92 39.65 41.28 7d compressive strength (MPa) 49.68 50.12 51.73 53.57 55.68 28d compressive strength (MPa) 52.36 53.64 55.68 57.57 58.43 3d flexural strength (MPa) 1.25 1.29 1.45 1.65 1.78 7d flexural strength (MPa) 4.56 4.75 4.76 4.83 6.21 28d flexural strength (MPa) 5.32 6.32 6.54 6.75 7.12 28-day chloride ion permeability rating IV IV IV IV IV Freeze-thaw 30 times mass loss (%) 0 0 0 0 0 Freeze-thaw 30 times dynamic modulus loss (%) 0 0.2 0.1 0.2 0.1 28 days carbonization depth (mm) 0.1 0.2 0.2 0.2 0.2 Volume shrinkage after 28 days 0.10 0.11 0.11 0.11 0.11

Claims

1. A method for preparing an early-strength, steam-free, high-content fly ash cement-based composite material, characterized in that: The steps include: Step 1: Mix 350-390 parts of cement, 780-840 parts of ultrafine fly ash, and 840-930 parts of fine fly ash uniformly according to weight to obtain component A; Step 2: According to the weight percentage, 9 to 14 parts of basic alumina, 8 to 13 parts of calcium oxide, 4 to 9 parts of calcium sulfate, 6 to 9 parts of sodium fluorosilicate, 7 to 10 parts of ultrafine hydrated calcium silicate and 4 to 7 parts of calcium formate are mixed and ground to obtain component B; Step 3, according to the mass parts, 9 to 14 parts of sulphoaluminate cement, 8 to 13 parts of polyaluminium sulfate, 11 to 13 parts of ultrafine silica powder and 7 to 10 parts of ultrafine acidic alumina are mixed and ground to obtain component C; Step 4: First, add 10 to 14 parts of a polymer activator solution with a solid content of 50% into 120 to 140 parts of water, according to the mass fraction, to obtain a diluted polymer activator solution; then add the diluted polymer activator solution into a mixture of 1970 to 2160 parts of component A, 38 to 62 parts of component B and 35 to 50 parts of component C, stir evenly, and obtain an early-strength, steam-free, high-content fly ash cement-based composite material.

2. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The cement in step 1 is ordinary Portland cement with a label of P·O 42.

5.

3. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The particle size of the ultrafine fly ash in step 1 is 0.4-0.6 μm, the particle size of the fine fly ash is 50-90 μm, and the ignition loss of the ultrafine fly ash and the fine fly ash is not more than 3.2%, the water requirement is not more than 91%, the water content is not more than 0.2%, the activity index is 85-90%, and the specific surface area is 2600-3100m 2 / kg.

4. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The particle size of the ultrafine hydrated calcium silicate in step 2 is 0.5-0.9 μm.

5. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The polyaluminium sulfate in step 3 has a basicity of 50% and a pH value of 5-9 in its aqueous solution.

6. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The ultrafine silicon dioxide powder in step 3 has a particle size of 0.2-0.6 μm, a loss on ignition of less than 3.0%, and a SiO2 content of more than 90%.

7. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The particle size of the ultrafine acidic alumina in step 3 is 0.3-0.8 μm.

8. The method for preparing the early-strength, steam-free, high-content fly ash cement-based composite material according to claim 1, characterized in that: The polymer activator solution in step 4 is a polyethyleneimine solution with a pH value of 9.0, and the average relative molecular mass of the polyethyleneimine is 3000.

9. An early-strength, autoclaved-free, high-content fly ash cement-based composite material prepared by the method according to any one of claims 1 to 8, characterized in that: The fly ash content is 72.63% to 74.41%, and the 3h compressive strength is greater than 12MPa.

10. Use of the early-strength, autoclaved-free, high-content fly ash cement-based composite material according to claim 9 in the preparation of cement-based composite material products.